Validity of Fetal Kidney Length for Gestational Age Estimation among Pregnant Women doing Antenatal Care in October 6 University Hospital - Hussein Mohamed Abdel Aal, Ahmed; Mohamed Said El-Azizi, Tarek; A. M. Abo Sheashaa, Hussien; Mostafa Assem, Mahmoud (Journal of Neonatal Surgery, 2025)
Background: Accurate gestational age (GA) estimation is crucial for optimal antenatal care, particularly in late-presenting pregnancies where conventional biometric parameters lose reliability. Fetal kidney length (FKL) has emerged as a potential alternative due to its consistent growth pattern and resistance to growth disturbances. Objective: This study aimed to evaluate the validity of FKL for GA estimation in the second and third trimesters compared to first-trimester crown-rump length (CRL) and conventional biometric parameters. Patients and Methods: A cross-sectional study was conducted at October 6 University Hospital, including 100 pregnant women (24–39 weeks) with documented first-trimester CRL. A single radiologist performed standardized ultrasound measurements of FKL (longitudinal pole-to-pole) and conventional parameters (BPD, HC, AC, FL). Statistical analysis included Pearson’s correlation, linear regression, Bland-Altman analysis, and mean absolute error (MAE) calculations. Results: FKL showed a strong correlation with CRL-based GA (*r* = 0.89, *p* < 0.001), with a linear growth rate of 1.32 mm/week (95% CI: 1.18–1.46). FKL-based GA estimation demonstrated superior accuracy (MAE = 0.8 weeks) compared to BPD (1.5 weeks), HC (1.3 weeks), AC (1.4 weeks), and FL (1.2 weeks). Bland-Altman analysis revealed minimal bias (0.3 days) between FKL and CRL-based GA. Right-left kidney measurements showed excellent agreement (ICC = 0.92). FKL also exhibited strong diagnostic performance for preterm/post-term classification (AUC 0.93 and 0.87, respectively). Conclusion: FKL is a reliable and accurate parameter for GA estimation in late pregnancy, outperforming conventional biometrics. Its consistent growth and reproducibility support its clinical adoption, particularly when early ultrasound dating is unavailable.